EFFECT OF COMBINATION OF HYPNOBREASTFEEDING AND ACUPRESSURE ON ANXIETY AND WOUND PAIN IN POST-CAESAREAN MOTHERS - Diah Evawanna Anuhgera; Tjahjono Kuncoro; Sri Sumarni; Mardiyono Mardiyono; Ari Suwondo (Belitung Raya Foundation, Indonesia, 2017)
Background: Post-cesarean mothers often experience anxiety and discomfort due to long-term pain. The combination of hypnobreastfeeding and acupressure is considered to be effective in reducing anxiety and pain levels. Objective: This study aims to examine the effect of combination of hypnobreastfeeding and acupressure on anxiety and pain levels in post-caesarean mothers. Methods: This study was a true experiment with pretest-posttest control group design, conducted in the Ambarawa Public Hospital Indonesia on 5 November to 9 December 2016. There were 36 participants selected using stratified random sampling, with 18 assigned in the experiment and control group. Data were analyzed using Paired t-test and Wilcoxon test. Results: There were statistically significant differences of anxiety and pain levels before and after intervention in the experiment and control group with p-value 0.001 (<0.05). Conclusion: The combination of hypnobreastfeeding and acupressure has a significant effect in reducing anxiety and pain levels in post-cesarean mothers. This intervention could be applied as an alternative therapy in treating post-caesarean mothers.